A magyar protestáns peregrináció a 16–18. században - Szögi, László (Gerundium, 2017)
Hungarian protestant peregrination in the 16th–18th century. Thanks to the researches of the last two decades nowadays we are able to nearly precisely determine the foreign educated Hungarian university students’ numbers and denominational affiliations. In the article I primary examined the order of magnitude of the catholic and protestant peregrination in the marked 3 centuries. In that era, the denominational characters of the different universities determined which students could attend their educations. Naturally, a few „tolerant” universities like Padova accepted students from every religion. In the research, we used the word „protestant” as generic term, because in the beginning of the 17th century it is nearly impossible to separate the Lutheran, Reformed and Unitarian students in the historical documents. The data of matriculations indicate that the protestant students represented a higher number in the Hungarian peregrination in every century however this fact was especially true for the 17th century. Namely, because the protestants usually matriculated at many different universities during their educations. Although, if we examine the summarized number of students who attended foreign education we gain nearly equal numbers about the Protestants and Catholics.